Influence of Leadership Style On Performance Employees of Stikes Bhakti Husada Bengkulu - Saputra, Wiwin; Susena, Karona Cahya; Anzori, Anzori (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
Employee performance is important in a company, because it has a great influence to improve company performance. Employee performance in the company is influenced by various things such as leadership style and job satisfaction. The purpose of this literature study and field study is to determine the leadership style on employee performance. The methodologies used are library research and field research. Respondents were 60 employees of Stikes Bhakti Husada Bengkulu using Simple Linear Regression analysis, Correlation Coefficient Analysis, Coefficient of Determination, and hypothesis testing using T-test. The results of the study The value of the correlation / relationship (R) is equal to 0.492. From these results obtained a coefficient of determination (R-Square) of 0.184, which implies that the influence of the independent variable (Leadership Style) on the dependent variable (Employee Performance) is 18.4% with the T-test results obtained f-value count of 13,045 with a significant value of 0.001 with an error rate of 0.5, it can be explained that there is a significant influence between leadership style on the performance of Stikes Bhakti Husada Bengkulu employees.